A Basic Monte Carlo Model of Initiated Chemical Vapor Deposition Using Kinetic Theory. Issue 1704 (29th August 2014) - Osman, Hayley R.; Mitra, Saibal
ABSTRACT: Initiated Chemical Vapor Deposition (iCVD) is a well-known method for depositing polymers that are used in chemical, biological, and electrical applications. It is a variation of hot filament deposition and can used to produce conformal coatings of polymer films at relatively low reaction temperatures. It is also a solventless technique in which thin polymeric films are deposited by introducing controlled ratios of monomer and initiator gasses into the reaction chamber. Low temperatures in the reaction chamber allow the deposition of polymer films on a wide variety of substrates that include biological substrates. We have simulated the growth of a monolayer of polymer films on two-dimensional surfaces using Monte Carlo simulation. We saw the formation of polymer chains over a time scale on the order of microseconds. We have assumed the substrate to be at room temperature while the reactor pressure close of 800 mTorr. The grid on which we have simulated this polymer growth is represented by a 100x100 matrix, on which a series of specialized functions are executed in each time-step, or iteration. These functions can be divided into three categories: population, translation, and polymerization. The goal of this simulation is to observe the initial growth of the iCVD surface reaction. We have obtained favorable results with the simulation and we are now looking to compare these results with experimental results for initiation growth.